Invasive Aspergillosis Due to Aspergillus Section Usti: A Multicenter Retrospective Study. (10th March 2020) - Glampedakis, Emmanouil; Cassaing, Sophie; Fekkar, Arnaud; Dannaoui, Eric; Bougnoux, Marie-Elisabeth; Bretagne, Stéphane; Neofytos, Dionysios; Schreiber, Peter W; Hennequin, Christophe; Morio, Florent; Shadrivova, Olga; Bongomin, Felix; et al.
Abstract: Background: Aspergillus spp. of section Usti ( A. ustus ) represent a rare cause of invasive aspergillosis (IA). This multicenter study describes the epidemiology and outcome of A. ustus infections. Methods: Patients with A. ustus isolated from any clinical specimen were retrospectively identified in 22 hospitals from 8 countries. When available, isolates were sent for species identification ( BenA / CaM sequencing) and antifungal susceptibility testing. Additional cases were identified by review of the literature. Cases were classified as proven/probable IA or no infection, according to standard international criteria. Results: Clinical report forms were obtained for 90 patients, of whom 27 had proven/probable IA. An additional 45 cases were identified from literature review for a total of 72 cases of proven/probable IA. Hematopoietic cell and solid-organ transplant recipients accounted for 47% and 33% cases, respectively. Only 8% patients were neutropenic at time of diagnosis. Ongoing antimold prophylaxis was present in 47% of cases. Pulmonary IA represented 67% of cases. Primary or secondary extrapulmonary sites of infection were observed in 46% of cases, with skin being affected in 28% of cases. Multiple antifungal drugs were used (consecutively or in combination) in 67% of cases. The 24-week mortality rate was 58%. A. calidoustus was the most frequent causal agent. Minimal inhibitory concentrations encompassing 90% isolates (MIC90 ) were 1, 8, >16, and 4 µg/mL for amphotericin B, voriconazole, posaconazole, and isavuconazole, respectively. Conclusions: Aspergillus ustus IA mainly occurred in nonneutropenic transplant patients and was frequently associated with extrapulmonary sites of infection. Mortality rate was high and optimal antifungal therapy remains to be defined. Abstract : Aspergillus group ustus (section Usti ) represents a rare cause of invasive aspergillosis (IA). This retrospective multicenter study reports the epidemiology and outcome of 72 cases of proven/probable IA due to this fungal pathogen.